Humanisms on the Verge of Collapse: The Nihilistamina Anime (2022)
This article presents a new type of protagonist developed in Japanese manganime: the nihilistamina heroes/heroines. Unlike the enthusiastic shōnen, hero the characters of some of the most popular titles in the medium sacrifice themselves for the survival of humanity despite their nihilistic view of the world, marked by trauma, institutional disaffection, and mental health issues. Through a narratological analysis of their roles, supported by a presentation of the context of humanitarianism in Japan, we offer a starting point for integrating this type of character into studies of the representation of humanitarianism in contemporary fiction.